OCT and OCT Angiography Offer New Insights and Opportunities in Schizophrenia Research and Treatment - Kyle M. Green; Joy J. Choi; Rajeev S. Ramchandran; Rajeev S. Ramchandran; Steven M. Silverstein; Steven M. Silverstein; Steven M. Silverstein; Steven M. Silverstein (Frontiers Media S.A., 2022)
The human retina and retinal imaging technologies continue to increasingly gain the attention of schizophrenia researchers. With the same embryologic origin as the brain, the retina offers a window into neurovascular changes that may underlie disease. Recently, two technologies that have already revolutionized the field of ophthalmology, optical coherence tomography (OCT), and a functional extension of this, optical coherence tomography angiography (OCTA), have gained traction. Together, these non-invasive technologies allow for microscopic imaging of both structural and vascular features of the retina. With ease of use and no side effects, these devices are likely to prove powerful digital health tools in the study and treatment of schizophrenia. They may also prove key to discovering disease relevant biomarkers that underly neurodevelopmental and neurodegenerative aspects of conditions such as schizophrenia.